Four new chrysophycean stomatocysts with true complex collar from the Shichengskoe raised bog in Central Russia - Kapustin, Dmitry A.; Philippov, Dmitriy A.; Gusev, Evgeniy S. (Phytotaxa, 2016)
Four new morphotypes of chrysophycean stomatocysts with true complex collar are described following International Statospore Working Group (ISWG) guidelines and illustrated by SEM micrographs. Stomatocyst 1 is ornamented with long ridges while three other morphotypes are ornamented with spines. Differences of our new morphotypes from known stomatocysts are discussed. We suppose that our stomatocysts are produced by acidobiontic and oligotraphentic species but biological affinity of them are currently unknown.